2018
DOI: 10.3126/jpan.v7i1.22934
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric morbidity among prisoners attending OPD of Central Jail Hospital, Kathmandu

Abstract: Introduction: Prisoners are one of the most vulnerable groups for having high prevalence of mental illness. There is a dearth of major studies conducted amongst prisoners in Nepal. The basic objective of this study is to study prevalence and nature of psychiatric morbidity in prisoners attending general OPD of Central jail Hospital, Kathmandu. Material and Method: This was a descriptive, cross-sectional study carried out in prisoners attending OPD of central jail for a period of six months. Initial scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(34 reference statements)
0
1
1
Order By: Relevance
“…11 Similarly, Valizadeh et al in their study done in Iran had found that prevalence of major depression was 42%, Baranyi et al in their study had revealed that, prevalence of major depression was 16%, and Bhattarai et al in Nepal, found that, prevalence of moderate depressive episode among 23.1% of the subjects which is higher than the present study. [12][13][14] So, it can be said that, in the present study though 100% of the population were found suffering from some grades of depression but the prevalence of severe depression was lesser than similar type of other studies.…”
Section: Discussioncontrasting
confidence: 49%
“…11 Similarly, Valizadeh et al in their study done in Iran had found that prevalence of major depression was 42%, Baranyi et al in their study had revealed that, prevalence of major depression was 16%, and Bhattarai et al in Nepal, found that, prevalence of moderate depressive episode among 23.1% of the subjects which is higher than the present study. [12][13][14] So, it can be said that, in the present study though 100% of the population were found suffering from some grades of depression but the prevalence of severe depression was lesser than similar type of other studies.…”
Section: Discussioncontrasting
confidence: 49%
“…In this research, F06.8 was included in the ten most diseases with 7.8% incidence. This is supported by research in a Nepalese prison hospital whose F06.8 is one of the ten most diseases with 2 of 121 inmates (1.7%)[8]. Research by Block and Calderón-Garcidueñas shows that the brain damage incidence is higher in industrial areas with lots of air pollutants[3].The research result by Block and Calderón-Garcidueñas differs from this research because densely industrialized districts do not have a high F06.8 incidence.…”
mentioning
confidence: 56%